Bioderecho y trasplante de órganos, muerte cerebral. (2013)
Knowing when life ends is a question on which there is still no answer. To thisend concepts have been established, such as brain or encephalic death, but thereis still no clear consensus among their definitions, and it is said they are termscreated specifically for organ transplantation. Currently, sciences such as medicineand biology have not found the elixir of eternal youth but they have achievedthe miracle of transplantation, thereby promoting actual mechanisms for the protectionof the human species. These mechanisms, although they proclaim stability andsatisfaction in people who can access them, they are not fair to the underprivileged.Therefore, it is clear the need for a symbiosis between the life sciences, the humansciences and legal science, to act from one same space regulating and questioningthemselves from an interdisciplinary environment, allowing the integration of new